The Role of House Prices in the Monetary Policy Transmission Mechanism in the U.S. - Hilde C. Bjørnland; Dag Henning Jacobsen (Norges Bank, 2008)
We analyze the role of house prices in the monetary policy transmission mechanism in the U.S. using structural VARs. The VAR is identified using a combination of short-run and long-run (neutrality) restrictions, allowing for a contemporaneous interaction between monetary policy and various asset prices. By allowing the interest rate and asset prices to react simultaneously to news, we find the role of house prices in the monetary transmission mechanism to increase considerably. In particular, following a monetary policy shock that raises the interest rate by one percentage point, house prices fall immediately by 1 percent, for then to decline by a total of 4-5 percent after three years. Furthermore, the fall in house prices enhances the negative response in output and consumer price inflation that has traditionally been found in the conventional literature.
hdl:11250/2497761
Keywords: C32; E52; F31; F41; 330; VAR; monetary policy; house prices; identification